Understanding COVID-19 vaccine hesitancy: A cross-sectional study in Malang District, Indonesia - Sujarwoto,; Maharani, Asri; Holipah,; Andarini, Sri; Saputri, Rindi Ardika Melsalasa; Pakpahan, Eduwin; Oceandy, Delvac; Tampubolon, Gindo (Frontiers in Public Health, 2023)
Vaccine hesitancy could undermine efforts to reduce incidence of coronavirus disease 2019 (COVID-19). Understanding COVID-19 vaccine hesitancy is crucial to tailoring strategies to increase vaccination acceptance. This study aims to investigate the prevalence of and the reasons for COVID-19 vaccine hesitancy in Malang District, Indonesia. Data come from a cross-sectional study among individuals aged 17-85 years old (N = 3,014). Multivariate ordered logistic regression was used to identify factors associated with postponing or refusing COVID-19 vaccines. The Oxford COVID-19 vaccine hesitancy scale was used to measure vaccine hesitancy. A wide range of reasons for hesitancy, including coronavirus vaccine confidence and complacency, vaccination knowledge, trust and attitude in health workers and health providers, coronavirus conspiracy, anger reaction and need for chaos, populist views, lifestyle, and religious influence, was examined. The results show that 60.2% of the respondents were hesitant to receive the COVID-19 vaccine. Low confidence and complacency beliefs about the vaccine (OR=1.229, 95% CI=1.195-1.264) and more general sources of mistrust within the community, particularly regarding health providers (OR=1.064, 95% CI=1.026-1.102) and vaccine developers (OR=1.054, 95% CI=1.027-1.082), are associated with higher levels of COVID-19 vaccine hesitancy. Vaccine hesitancy is also associated with anger reactions (OR=1.019, 95% CI=0.998-1.040), need for chaos (OR=1.044, 95% CI=1.022-1.067), and populist views (OR=1.028, 95% CI=1.00-1.056). The findings were adjusted for socio-demographic factors, including age, sex, education, marital status, working status, type of family, household income, religious beliefs, and residency. The results suggest the need for an effective health promotion program to improve community knowledge of the COVID-19 vaccine, while effective strategies to tackle “infodemics” are needed to address hesitancy during a new vaccine introduction program.